1995
DOI: 10.1002/jlb.57.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endotoxin on expression of VLA integrins by human bronchoalveolar lavage macrophages

Abstract: Endotoxin (lipopolysaccharide, LPS) is known to induce inflammatory responses, such as monocyte/macrophage adherence, migration, and accumulation. Recruitment and accumulation of macrophages during infection and inflammation are regulated by integrin-mediated cell-extracellular matrix interactions. In the present report, we studied the effects of LPS on the expression of VLA-5 (alpha 5 beta 1), VLA-3 (alpha 3 beta 1), and VLA-2 (alpha 2 beta 1) integrins and fibronectin (FN) by human alveolar macrophages in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…As with surfactant proteins, this interaction may not directly facilitate phagocytosis by the alveolar macrophages, although it is known that other actions of the macrophages, such as the release of tumor necrosis factor alpha, are enhanced by this interaction (44). Typically, these adhesion molecules bind to subsets of integrins on the surface of macrophages and other cells (6), many of which exhibit dynamic changes in expression during periods of inflammation (24,25). Finally, immunoglobulins against P. carinii can potentially opsinize Pneumocystis organisms and promote phagocytosis or extracellular killing of the pathogens, although the importance of this during in vivo infections is still not clear (reviewed in reference 2).…”
Section: Discussionmentioning
confidence: 99%
“…As with surfactant proteins, this interaction may not directly facilitate phagocytosis by the alveolar macrophages, although it is known that other actions of the macrophages, such as the release of tumor necrosis factor alpha, are enhanced by this interaction (44). Typically, these adhesion molecules bind to subsets of integrins on the surface of macrophages and other cells (6), many of which exhibit dynamic changes in expression during periods of inflammation (24,25). Finally, immunoglobulins against P. carinii can potentially opsinize Pneumocystis organisms and promote phagocytosis or extracellular killing of the pathogens, although the importance of this during in vivo infections is still not clear (reviewed in reference 2).…”
Section: Discussionmentioning
confidence: 99%
“…In context of this observation, it is interesting that adhesion molecule expression on in vitro-generated human M2 macrophages (M-CSF derived) is more sensitive to CCL1 than that on M1 macrophages (GM-CSF derived). Kang et al have previously demonstrated that prolonged exposure to LPS downregulates expression of certain VLA components, while brief transient exposure upregulates expression (18). Our observations suggest that M2 macrophages may be more involved in conditions such as peritoneal adhesion surgery complications and that CCL1 may play a contributing role.…”
Section: Discussionmentioning
confidence: 49%
“…decrease in macrophage phagocytosis of yeast (Sandstrom et al, 1992), and treatment of AM with LPS decreased the expression of various b 1 integrins including fibronectin receptors (Kang et al, 1995). Data showed that the chemiluminescence response to opsonized zymosan was not affected by endotoxin in either MO or AM, but was decreased by UAP.…”
Section: Discussionmentioning
confidence: 96%